Desarrollo del ecoturismo en la asociación de protección flora y fauna en el sector del Alto Shilcayo y Tamushal en el área de conservación regional cordillera escalera entre los años 2001 al 2008 - Muñoz Macedo, Magna Elena (2010)
This research studied the significance of the development of ecotourism in the Association of Protection of Flora and Fauna in the Field of High Shilcayo and Tamushal from 2001 to 2008, located within the Regional Conservation Area Cerro Escalera and created more than 7 years. The instruments and techniques used to the significance of development, they were checking documents, structured interviews, experiential observation and documents certifying the formality of the s:e. The results were that Ecotourism development ecotourism in the Association of Protection of Flora and Fauna in the Field of High Shilcayo and Tamushal from 2001 to 2008 has been significant. This is due to the marked growth of tourism in the city of Tarapoto, and especially the preference of visitors to ecotourism, been demonstrated the promise of increased benefits not only to association members but also the surrounding residents and the city of Tarapoto.